STRATEGI PROGRAM HALO USTAD DI SALAM TV DALAM MENARIK MINAT KHALAYAK UMUM - Ari Oldwin Sitorus; Wirdatul Wisfa; Nurhalimah Br. Manik; Amran Sahputra Tanjung (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
The problem in this research is what is the strategy for the halo ustad program in attracting audience interest on salam tv. This study aims to find out how the strategy in the Halo Ustad program is to attract public interest on Salam TV. This study uses a qualitative method. Data collection was carried out using observation techniques and direct interviews at the research location. The strategy in the halo ustad program starts with compiling a broadcast schedule, choosing and preparing questions, choosing a teacher to present the program, which is very influential on the intended audience. For that we need a strategy in an event program.